Developing an Islamic Values-Based Digital Learning Framework for Early Childhood Education: A Systematic Literature Review - Dwi Feskariani; Elce Purwandari; Wildan Miftahussurur; Afifah Wahyuningsih (Civiliza Publishing, Indonesia., 2026)
The rapid advancement of digital technology has transformed early childhood education, creating both opportunities and challenges for integrating educational innovation with religious and moral development. Although numerous studies have examined digital learning and Islamic education independently, limited research has synthesized these perspectives into a comprehensive conceptual framework for early childhood education. This study aims to synthesize the existing literature on Islamic values-based digital learning and propose a conceptual framework to support future educational practice and research. A systematic literature review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant studies published between 2015 and 2026 were retrieved from Scopus, Web of Science, ERIC, and Dimensions using predefined search strategies and eligibility criteria. The selected studies were analyzed through thematic synthesis to identify recurring patterns, research trends, and core conceptual dimensions. The findings reveal that effective digital learning in early childhood education depends on the integration of six interconnected dimensions: Islamic values, digital pedagogical design, teacher competence, parental engagement, technological infrastructure, and holistic child development. The review also demonstrates that Islamic values should function as the philosophical foundation guiding the design and implementation of digital learning rather than merely serving as complementary instructional content. Based on these findings, this study proposes the Islamic Values-Based Digital Learning Framework for Early Childhood Education, providing a theoretical foundation for future empirical research and practical guidance for educators, curriculum developers, and policymakers seeking to implement meaningful, ethical, and developmentally appropriate digital learning in Islamic educational settings.